Exploring resources and capabilities factors among entrepreneurial ventures using DEMATEL approach - Olamitunji Dakare; Sulaimon Olanrewaju Adebiyi; Bilqis Bolanle Amole (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
Resources and capabilities remain one of the most important factors that influence firms, more especially entrepreneurial ventures, to improve their competitiveness and achieve competitive advantage. In this context, present paper explores how entrepreneurial ventures and small businesses can better identify and distinguish the cause-and-effect relationship amongst resource and capability factors. Resource and capability factors among entrepreneurial ventures were classified into three dimensions and fourteen criteria after a review of the literature. The study applied the Decision-Making Trial and Evaluation Laboratory (DEMATEL) model to identify and describe the cause-and-effect relationship amongst resource and capability factors. The findings reveal that in prioritizing the importance of criteria and cause-and-effect relationship among criteria under the three core dimensions, firm climate, managerial competence, market knowledge and technological capabilities and equipment were the most critical criteria. Furthermore, the result has shown that firm climate is the most significant criterion in the adjustment of resource and capability factors of entrepreneurial ventures. Therefore, promoting a supportive and conducive firm climate among entrepreneurial ventures can enhance other resources and capabilities factors which, in turn, will improve the overall performance of entrepreneurial ventures and small businesses.
Keywords: M13; 330; Resources; capabilities; entrepreneurial ventures; small businesses; DEMATEL